2005
DOI: 10.1677/jme.1.01745
|View full text |Cite
|
Sign up to set email alerts
|

The post-endocytotic fate of the gonadotropin receptors is an important determinant of the desensitization of gonadotropin responses

Abstract: Internalization of the ligand/receptor complexes is a consequence of the activation of the gonadotropin receptors. Since the recycling or degradation of the internalized receptors results in the maintenance or loss of cell surface receptors respectively and this contributes to the loss of responsiveness, we hypothesized that the fate of the internalized receptors could be an important component of desensitization. We examined this hypothesis using the wild-type and mutants of the human LH (hLHR) receptors and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 47 publications
2
35
0
Order By: Relevance
“…The relative ability of FSH glycoforms to bind the FSHR was not affected by the numbers of FSHR present in the ligand-binding assay, since testis homogenates and CHO cells, which overexpress the FSHR, represent conditions of low vs high receptor density, respectively. This information is useful for the present analysis since others have shown that cellular signaling responses to FSH, such as cAMP accumulation (26), are proportional to the number of occupied receptors. It seems, therefore, that the extent of FSH␤ subunit N-glycosylation may contribute to the ability of FSH to activate the cAMP/PKA signaling pathway in granulosa cells.…”
Section: Discussionmentioning
confidence: 99%
“…The relative ability of FSH glycoforms to bind the FSHR was not affected by the numbers of FSHR present in the ligand-binding assay, since testis homogenates and CHO cells, which overexpress the FSHR, represent conditions of low vs high receptor density, respectively. This information is useful for the present analysis since others have shown that cellular signaling responses to FSH, such as cAMP accumulation (26), are proportional to the number of occupied receptors. It seems, therefore, that the extent of FSH␤ subunit N-glycosylation may contribute to the ability of FSH to activate the cAMP/PKA signaling pathway in granulosa cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore it is possible that cytohesin 2 mediates ARF6 activation downstream of LHCGR. LHCGR internalises following its activation, which regulates the biological responsiveness of the receptor (Bhaskaran and Ascoli, 2005). The inhibition of LHCGR internalisation increases the density of cell surface receptors and thereby AC activation with consequent increase in cAMP accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…LHCGR internalisation and recycling regulate the density of cell surface receptors and thereby the sensitivity of the cells to LH (Bhaskaran and Ascoli, 2005). ARF6 is a member of the ARF family of small GTPases, which regulates membrane trafficking by cycling between the active GTP-and inactive GDP-bound states (Donaldson and Jackson, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…An important aspect of LHCGR activity and its regulation is the internalization of agonist-activated receptors into the intracellular compartments of the cell (48). ARF6 regulates the internalization of LHCGR as well as that of other GPCRs (11,22), however, the molecular mechanisms underlying ARF6 involvement in GPCR trafficking are not well understood.…”
Section: Discussionmentioning
confidence: 99%